Dose Response Effect of High-Dose Fluconazole for HIV-Associated Cryptococcal Meningitis in Southwestern Uganda - Longley, Nicky; Muzoora, Conrad; Taseera, Kabanda; Mwesigye, James; Rwebembera, Joselyne; Chakera, Ali; Wall, Emma; Andia, Irene; Jaffar, Shabbar; Harrison, Thomas S. (Clinical infectious diseases, 2008)
Background. Therapy for human immunodeficiency virus (HIV)–associated cryptococcal meningitis in many centers in Africa is fluconazole administered at a dosage of 400–800 mg per day. However, higher dosages of fluconazole have been used to treat patients without resulting in serious toxicity. Pharmacokinetic and pharmacodynamics considerations suggest that higher dosages might be associated with greater efficacy. Methods. Sixty HIV-seropositive, antiretroviral therapy–naive patients with first-episode cryptococcal meningitis in Mbarara, Uganda, were treated with fluconazole: the first 30 patients received 800 mg per day, and the second 30 patients received 1200 mg per day. After 2 weeks, the dosage was reduced to 400 mg per day for an additional 8 weeks. The primary outcome measure was rate of clearance of infection, or early fungicidal activity, as determined by serial quantitative cerebrospinal fluid cryptococcal cultures during the first 2 weeks. Secondary outcome measures were safety and mortality through 10 weeks. Results. Forty-seven percent of patients had a reduced level of consciousness at presentation. Early fungicidal activity was significantly greater for patients receiving fluconazole at a dosage of 1200 mg per day than it was for patients receiving 800 mg per day (early fungicidal activity _ standard deviation, _0.18_0.11 vs. _0.07_ 0.17 log colony-forming units/mL per day; Pp.007). Fluconazole administered at a dosage of 1200 mg per day appeared to be well tolerated, and no liver function disturbance was observed. Two-week and 10-week mortality were 30% and 54%, respectively, with no statistically significant difference between the groups. Conclusions. Fluconazole is more rapidly fungicidal when administered at a dosage of 1200 mg per day than when administered at a dosage of 800 mg per day. In resource-limited settings, additional studies are needed to test the addition of flucytosine or short-duration amphotericin B to high-dose fluconazole and to test strategies to facilitate earlier presentation, diagnosis, and treatment of patients with cryptococcal meningitis
Keywords: Dose Response Effect; Cryptococcal Meningitis; HIV; Uganda; High-Dose